Cathodic protection-sacrificial anode design - Rosario Francia, Samuel (2004)
Cathodic protection consists of forcing the structure to function as a cathode in a corrosion cell, by manipulating and / or modifying electrochemical factors. A galvanic anode, also called a sacrificial anode, if electrically connected to a submerged structure will discharge a current that will flow through the electrolyte to the structure it is intended to protect. To meet this objective, the anodes must meet certain characteristics of weight, dimensions, geometric shape. This work aims to lead the design engineer for cathodic protection systems with sacrificial anodes to obtain the appropriate anode by a simple method.